Influence Use of Clay Soil With Additions Fly Ash (Rock Ash) Against Soil Classification Properties and CBR - Laia, Rahmat Abadi; Nasution, Ridwan; Lubis, , Muhammad Yusuf Parlagutan (International Journal of Mechanical Computational and Manufacturing Research, 2025)
Soil is the basis of a road foundation, building and also in a civil work where the material consists of an aggregate (granules) or solid minerals that are cemented (chemically bound) to each other from organic materials that have weathered (which particulate matter accompanied by liquid and gas that fills an empty space between the solid particles) The additive used in this research is fly ash. The method used in this research is the experimental method, namely a method carried out by conducting an experiment to obtain data. Based on the results of research testing on the use of clay soil and the addition of fly ash, the CBR value was obtained after being corrected with a percentage of 100% clay soil, and 0% fly ash obtained a CBR value of 6.06% with a soil classification of A-7-6. The use of 75% clay soil and 25% fly ash obtained a CBR value of 15.20% with soil classification A-5. The percentage of use of 50% clay soil and 50% fly ash results in a CBR value of 18.15% with classification A-4. The CBR value and soil classification are better for 50% clay soil and 50% fly ash.